2018
DOI: 10.1093/jxb/ery022
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gibberellin functions during and after grapevine bud dormancy release

Abstract: Gibberellin has an inhibitory effect during initial activation of dormant grapevine buds, and at this stage its level is down-regulated. At a later stage, gibberellin level increases and enhances bud regrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 72 publications
(111 reference statements)
3
43
0
Order By: Relevance
“…Interestingly, we highlighted PavGASA6 and PavGA20ox1, two genes associated with the gibberellin pathway. In particular, PavGA20ox1, that encodes an enzyme required for the biosynthesis of active GA (Plackett et al 2012), is markedly upregulated after endodormancy release, associated with H3K4me3 enrichment at the locus, therefore, suggesting that epigenetic and transcriptomic states facilitate an increase in active GA levels during ecodormancy, as previously shown in hybrid aspen (Rinne et al 2011) and grapevine (Zheng et al 2018).…”
Section: Genes Involved In Bud Dormancysupporting
confidence: 55%
“…Interestingly, we highlighted PavGASA6 and PavGA20ox1, two genes associated with the gibberellin pathway. In particular, PavGA20ox1, that encodes an enzyme required for the biosynthesis of active GA (Plackett et al 2012), is markedly upregulated after endodormancy release, associated with H3K4me3 enrichment at the locus, therefore, suggesting that epigenetic and transcriptomic states facilitate an increase in active GA levels during ecodormancy, as previously shown in hybrid aspen (Rinne et al 2011) and grapevine (Zheng et al 2018).…”
Section: Genes Involved In Bud Dormancysupporting
confidence: 55%
“…Along with the chilling accumulation, ABA levels increased, which confirmed a relationship with bud dormancy maintenance [31,32]. While the buds chilling accumulation was enough, endogenous ABA levels were down-regulated and GA 3 level in flower buds were up-regulated during the dormancy release [33][34][35]. Our previous studies showed that hydrogen cyanamide improved GAs:ABA ratio, resulting in the endodormancy release and blooming in sweet cherry [36], and hydrogen cyanamide could down-regulate the expression levels of DAMs in peach [15].…”
Section: Discussionmentioning
confidence: 54%
“…GA 3 has been shown to modulate the growth and development of plants, mainly by stimulating mitotic division and cell elongation 39,40 . The positive effects of GA 3 on bud break have been reported in the tissue culture of woody plant species [41][42][43][44] . However, adding the improper concentration of GA 3 has a negative effect.…”
Section: Resultsmentioning
confidence: 99%